Les taxes en ancienne Pologne (XIV/XV-XVIII siècles). Types, mécanisme d’edition, domaine, destinataires, forme et langage [Taxes in Old Poland (14th/15th-18th centuries). Types, publication mechanism, scope, recipients, form and language] - Chodyła, Zbigniew (Studia Historiae Oeconomicae, 2001)
In the period from the 14th/15th to the 18th century, more than ten types of taxes were formed and operated in Poland, depending on the legal status of their official publishers, which, in addition, differed from each other by the mechanism, i.e. by the manner (apparatus) and frequency of their publication, their thematic (although not always), temporal and territorial sphere, sometimes by the categories (social, professional, organizational-professional and even confessional and national) of their recipients, as well as by their formal and legal character.